Fatherland - Harris, Robert, 1957- (London : Arrow Books, 2009)
Berlin, 1964, Hitler is about to celebrate his seventy-fifth birthday and President Joseph P. Kennedy is to visit Berlin to initiate detente with Germany.
.
Adult.
Adult
Keywords: Hitler, Adolf, -- 1889-1945 -- Fiction; Hitler, Adolf, -- 1889-1945 -- Fiction; Presidents -- United States -- Fiction; Germany -- Fiction; Adventure stories; Alternative histories